Lymphotoxin-α C804A polymorphism and the presence of simple endometrial hyperplasia in Egyptian women. Issue 1 (1st January 2021) - refaat, Manar
ABSTRACT: Endometrial hyperplasia (EH) is found to be a common diagnosis in women presenting with abnormal uterine bleeding, in advanced stages leading to cancer. To test the association of endometrial hyperplasia with the lymphotoxin-α (LT-α) C804A polymorphism, a case–control study was performed in Egyptian subjects. The cases comprised 100 endometrial hyperplasia patients, and the controls were 120 females served as control. Results showed that C allele versus A allele was compared in Simple Endometrial hyperplasia (SEH) cases compared to controls, there was no significant difference. In pre-menopausal cases, using the CC genotype as the reference genotype, the CA genotype was associated with a significantly elevated OR of 3.36 (95% CI =1.3–8.2, P = 0.007) in SEH cases compared to control. In addition, dominant genotypes (AA plus CA) were significantly increased in SEH cases compared to controls (OR =0.36, 95% CI =0.15–0.84, P =0.01). In conclusion, the common Lymphotoxin- α C804A polymorphism gene is associated with an increased risk of simple endometrial hyperplasia.